Survival and quality of life for patients with COPD or asthma admitted to intensive care in a UK multicentre cohort: the COPD and Asthma Outcome Study (CAOS). Issue 2 (13th October 2008) - Wildman, M J; Sanderson, C F B; Groves, J; Reeves, B C; Ayres, J G; Harrison, D; Young, D; Rowan, K
Abstract : Background: Non-invasive ventilation is first-line treatment for patients with acutely decompensated chronic obstructive pulmonary disease (COPD), but endotracheal intubation, involving admission to an intensive care unit, may sometimes be required. Decisions to admit to an intensive care unit are commonly based on predicted survival and quality of life, but the information base for these decisions is limited and there is some evidence that clinicians tend to be pessimistic. This study examined the outcomes in patients with COPD admitted to the intensive care unit for decompensated type II respiratory failure. Methods: A prospective cohort study was carried out in 92 intensive care units and 3 respiratory high dependency units in the UK. Patients aged 45 years and older with breathlessness, respiratory failure or change in mental status due to an exacerbation of COPD, asthma or a combination of the two were recruited. Outcomes included survival and quality of life at 180 days. Results: Of the 832 patients recruited, 517 (62%) survived to 180 days. Of the survivors, 421 (81%) responded to a questionnaire. Of the respondents, 73% considered their quality of life to be the same as or better than it had been in the stable period before they were admitted, and 96% would choose similar treatment again. Function during the stable pre-admission period was a reasonable indicator of function reported by those who survived 180 days. Conclusions: Most patients with COPD who survive to 180 days after treatment in an intensive care unit have a heavy burden of symptoms, but almost all of them—including those who have been intubated—would want similar intensive care again under similar circumstances.